Description of the male of Sebasthetops omaliniformis Jäch, 1998 —a phylogenetically isolated water beetle from South Africa, with notes on its ecology (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2013)
Sebasthetops omaliniformis Jäch, 1998, is a morphologically aberrant hydraenid, known from two female specimens collected from the Western Cape of South Africa in 1988. Recent fieldwork has resulted in the rediscovery of the species, close to the type locality. The male of S. omaliniformis is described from this material, and the opportunity taken to publish a record of Sebasthetops from the Langeberg, where it was collected in 1979. S. omaliniformis lives in deep water riffles in the upper reaches of mountain streams, and is strongly brachypterous. Like a number of other running-water insects known from theCape fold mountains the species appears to have a narrow geographical and ecological range, deserving of high conservation status.